Analysis of Coupling Losses for All-Fiber Integration of Subwavelength Core Hybrid Optical Fibers - Yucheng Ye; Limin Xiao; Shaohua Dong; Anna C. Peacock (IEEE Photonics Journal, 2018)
Coupling losses for all-fiber integration of subwavelength core hybrid optical fibers have been first analyzed and optimized in detail. We have taken into account the effects of mode size, mode shape, effective refractive index, tapering beat length, interface, and endface reflections on the coupling loss. By optimizing parameters such as the subwave-length core diameter, single mode condition, and transition length, the coupling losses can be reduced. In addition, the influence of the core fabrication and misalignment tolerances have been explored. The results will benefit the all-fiber integration of hybrid optical fibers and their nanoengineering realization.